2012
DOI: 10.2147/clep.s35693
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric sepsis in the developing world: challenges in defining sepsis and issues in post-discharge mortality

Abstract: Sepsis represents the progressive underlying inflammatory pathway secondary to any infectious illness, and ultimately is responsible for most infectious disease-related deaths. Addressing issues related to sepsis has been recognized as an important step towards reducing morbidity and mortality in developing countries, where the majority of the 7.5 million annual deaths in children under 5 years of age are considered to be secondary to sepsis. However, despite its prevalence, sepsis is largely neglected. Applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 28 publications
2
51
0
1
Order By: Relevance
“…The incidence of pediatric sepsis is higher in developing country where pathogens readily invade children because of low birth weight, water and air pollution as well as insufficient immunization and nutrition [3,4]. Pediatric sepsis is a spectrum of disorders that mainly infected by bacteria, viruses, fungi, parasites or the toxic byproducts of these microorganisms [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of pediatric sepsis is higher in developing country where pathogens readily invade children because of low birth weight, water and air pollution as well as insufficient immunization and nutrition [3,4]. Pediatric sepsis is a spectrum of disorders that mainly infected by bacteria, viruses, fungi, parasites or the toxic byproducts of these microorganisms [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia, diarrhea, and malaria were the leading infectious causes of death [1]. Sepsis represents the progressive underlying inflammatory pathway secondary to any infectious illness, and ultimately is responsible for most infectious disease-related deaths [2].…”
Section: Introductionmentioning
confidence: 99%
“…Though Goldstein et al's definitions were designed for research purposes, they are often used clinically in developed nations for identification of children who have lifethreatening infections requiring urgent intervention. More importantly, they form the basis for the development of guidelines aimed at treating the various stages of the sepsis continuum [2].…”
Section: Introductionmentioning
confidence: 99%
“…1 Sepsis, according to the Pediatric Consensus Conference definition, is the systemic response to any infectious disease which can progress from a mild inflammatory derangement (systemic inflammatory response syndrome) to multi-organ failure, shock and death 2 , and therefore, can be broadly considered to be the primary cause of acute infectious disease death. 3 While the period of acute illness is well known to account for much of this burden, relatively little is known about the epidemiology of the post-acute period and its contribution to overall infectious disease associated mortality. A recent systematic review has found that the months following hospital discharge account for at least as many deaths as the hospital period.…”
Section: Introductionmentioning
confidence: 99%
“…The identification of vulnerable children is an important first step in addressing this important public health problem. 3 Research aimed at creating tools to aid in such identification must ensure that the most important and relevant predictors are included for analysis in order to optimize model development. 5,6 The method by which candidate predictors are selected vary widely among studies and many include informal discussions among the research team and colleagues or more formal methods such as focus group discussions, questionnaires and surveys.…”
Section: Introductionmentioning
confidence: 99%